Pengembangan Sistem informasi Pemantauan Ibu Hamil Berisiko di Puskesmas Ngemplak Simongan Semarang - Ulfah Fachrun Nisa; Arif Kurniadi (Dian Nuswantoro Semarang, 2016)
The monitoring of pregnant women at risk in the clinic is very important, not only giving information about risk factors but also providing treatment during pregnancy and childbirth. Treatment of pregnant women during pregnancy, childbirth and postpartum is needed to reduce the risks that can occur during pregnancy, childbirth, and postpartum. Maternal mortality is also one of the targets of Millennium Development Goals (MDGs), that is the fifth goal, to improve maternal health. Puskesmas Ngemplak Simongan had many obstacles on the monitoring system of pregnant women at risk, such as there is no information system to monitor the pregnant women. This research aims to design the information system for pregnant women at risk to in PHC Ngemplak Simongan Semarang.This was qualitative descriptive study by applying the method of system development life cycle approach. The subjects of this study were Meternal and Children Health officers, theywere the head of public health center. The object was the Information System for Pregnant Women at risk monitoring in Ngemplak Simongan Public Health Center.The result of this research was an information system that was useful for monitoring of pregmant women at risk. The information system simplify the process of data input and expedite data delivery to health office. The implementation of the information system in Public Health Center can be used as a tool to monitor pregnant women at risk in order to reduce maternal risk and maternal mortality.Keywords: Information Systems, Monitoring Pregnant Women at Risk